Ruminal degradability of organic matter of varieties of drought tolerant Cenchrus purpureus - Ledea Rodríguez, José Leonardo (2018)
The main limitation of tropical grasses is their high content of structural carbohydrates, which determine the use of grass by animals. When pastures or forages grow in adverse ecosystems there are important changes in the ruminal degradability of the compounds of interest. The objective was to characterize, at different ages of regrowth, the in situ ruminal degradability of the organic matter of different varieties of Cenchrus purpureus genetically improved to tolerate dry environments. Three drought tolerant varieties (CT-601, CT-603, and CT-605) were taken at different regrowth ages (60, 80, 100, and 120 days). Two fistulated Creole cows of 400 ± 50 kg of live weight were used. The bags were introduced in the rumen for 0, 4, 6, 8, 12, 24, 48, and 72 hours, the estimation of the rumen degradation was made fitting the data to the exponential equation (a + b) * (1-e (-c * t)). The best performance in situ ruminal degradability of the potentially degradable fraction (a + b) of leaves was observed at the age of eighty days, while the effect of the degradation dynamics due to the effect of regrowth age was common for leaves and stems. Fraction degradation values did not exceed 10% for leaves and stems; however, the degradation of b showed values that exceeded 71% for leaves and 30% for stems. The new varieties showed a ruminal fermentation pattern close to 50%, characteristic of tropical grasses.